The Identification of Araliaceae Species by ITS2 Genetic Barcoding and Pollen Morphology - Reunov, Arkadiy; Reunova, Galina; Atopkin, Dmitry; Reunova, Yulia; Muzarok, Tamara; Zakharov, Evgeny; Zhuravlev, Yury (Planta Medica, 2018)
The genetic barcode ITS2 (ITS: internal transcribed spacer) and pollen morphology were used for the identification of the pharmacologically valuable wild Araliaceae species Panax ginseng, Oplopanax elatus, Aralia elata, Aralia continentalis, Eleutherococcus senticosus, and Eleutherococcus sessiliflorus inhabiting the natural forests of Primorye, Russia. The ITS2 locus successfully identified all six species, which supports the use of ITS2 as a standard barcode for medicinal plants. However, the ITS2 locus was insufficient for intra-specific discrimination in these species, neither within Primorye nor from other world representatives within GenBank. Araliaceae pollen was confirmed to undergo size-reducing metamorphosis. The final morphotypes were species-specific for each of the six species but could not discriminate intra-species geographic localities within Primorye. The morphologies of the final pollen morphotypes from homologous species inhabiting other parts of the world are not yet known. Therefore, whether pollen is applicable for Araliaceae intra-species discrimination between Primorye and other world localities could not be established. Based on these findings, we propose that the ITS2 genetic barcode and the final pollen morphotypes are suitable for the identification of Araliaceae species. However, further studies will be needed to determine the suitability of genetic and pollen traits for Araliaceae geographic authentication.
Keywords: Araliaceae; DNA barcoding; ITS2; pollen